Raising the summit or flattening the agora? The elitist turn in science policy in Northern Europe. Issue 4 (2nd October 2017) - Geschwind, Lars; Pinheiro, Rómulo M.
ABSTRACT: This contribution focuses on how one hegemonic idea – excellence – which has significant impact on science and higher education policy was translated in two Nordic countries: Norway and Sweden. Building on key concepts emanating from political science and organizational sociology, the article assesses how excellence was locally translated by policy makers, leading to the rise of a series of policy measures aimed at fostering excellence in science across the board. In doing this, we investigate a key empirical dimension: the policy mechanisms or instruments launched at national levels (two Nordic countries) in the form of centers of excellence.